2008
DOI: 10.1089/jmf.2007.0144
|View full text |Cite
|
Sign up to set email alerts
|

New Functional ProbioticLactobacillus sakeiProbio 65 Alleviates Atopic Symptoms in the Mouse

Abstract: The purpose of this study was to investigate the improvement of allergic dermatitis in chemical allergen-induced mice by Lactobacillus sakei probio 65. L. sakei probio-65 was isolated from kimchi, a traditional Korean fermented food. This strain was resistant to gastric acidity, bile, and several antibiotics and possessed antimicrobial activity against several pathogenic microorganisms. To investigate whether the probiotic activity of L. sakei probio 65 was effective for treating allergic dermatitis, the organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 38 publications
0
36
0
1
Order By: Relevance
“…In another study, Lctbs plantarum strains from Kimchi were investigated for their capacity to inhibit AD (house dust mite-induced dermatitis) in NC/Nga mouse. The three strains, CJLP55, CJLP133, and CJLP136, suppressed AD-like skin lesions and epidermal thickening [13, 23, 87]. …”
Section: Experimental (Animal Model) and Clinical (Human) Studies mentioning
confidence: 99%
“…In another study, Lctbs plantarum strains from Kimchi were investigated for their capacity to inhibit AD (house dust mite-induced dermatitis) in NC/Nga mouse. The three strains, CJLP55, CJLP133, and CJLP136, suppressed AD-like skin lesions and epidermal thickening [13, 23, 87]. …”
Section: Experimental (Animal Model) and Clinical (Human) Studies mentioning
confidence: 99%
“…It also has an anti-inflammatory role by mediating the release function of lysosome and the chemotaxis of neutrophils to inhibit sebaceous differentiation. In clinical settings, topical application of retinoic acid drugs can be used to treat acne and keratinized skin with a definite curative effect (Kozono et al, 2002;Park et al, 2008). However, one of its inevitable side effects is skin and mucosa dryness.…”
Section: Discussionmentioning
confidence: 99%
“…However, we chose L. sakei probio 65 as it was used in two studies previously. Park et al10 described an animal study involving the oral administration of L. sakei probio 65 in which the treated group exhibited better clinical improvement and lower interleukin (IL)-4 and immunoglobulin (Ig)-E levels than the control group. In addition, a 12-week, double-blind, placebo-controlled trial showed that oral administration of L. sakei probio 65 resulted in clinical improvement of patients with AD11.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various strains of this bacterium, L. sakei probio 65, exhibited the most potent inhibitory activity against Staphylococcus aureus growth in preliminary experiments. It also induced immunological and clinical improvements in an animal study and a clinical study10,11. The present clinical trial was performed to determine whether the efficacy of emollients in AD could be improved by incorporating L. sakei .…”
Section: Introductionmentioning
confidence: 99%